Dietary intake and micronutrient deficiency in children with cancer. Issue 10 (9th July 2019) - Morrell, Miriam B. G.; Baker, Rebecca; Johnson, Abigail; Santizo, Ruth; Liu, Diane; Moody, Karen
Abstract: Data regarding micronutrient deficiencies in children with cancer are lacking. We measured micronutrients in a subset of children with cancer (n = 23) participating in a randomized trial of the neutropenic diet. Ninety‐six percent of children had ≥1 micronutrient deficiency and 39% had ≥3 micronutrient deficiencies. Eighty‐six percent of children had vitamin C deficiency, 87% had 25‐hydroxyvitamin D deficiency, 50% had zinc deficiency, and 13% had vitamin A deficiency. Dietary intake did not correlate with micronutrient deficiency status. More data are needed regarding the prevalence and etiology of micronutrient deficiencies in children with cancer to further understand their implications and treatment.